Cost Model Estimasi Konseptual Untuk Bangunan Gedung Rumah Sakit - Aptiyasa, Putu A.A.; Effi, Cosmas P.Y Pao; Rada, Stefanus (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2025)
Implementation of the hospital building project, have a ways of estimation in accordance with the phases of the project. In the early stages of project planning, (owner) requires the estimated cost to construct the project budget. So it is necessary to develop cost estimation model that is easy to use, accurate and reliable. This research planning to develop a model estimation on stage initial project planning, easy with a fairly accurate results. Development method uses the principle of " Cost Significant Model" and the multiple linear regression. 6 data obtained using the method of work packages BoQ (Bill of Quantity) hospital building with details of data among 5 work packages that have been realized from fiscal year 2011 - 2014 were compared with 1 package of work to be performed